Quality of cold-stored free-range eggs sold in different retail outlets in Alfenas – MG, Brazil - Isabella de Jesus Oliveira; Ana Patrícia Alves Leão; Ana Gabriela Costa Cordeiro; Fernanda de Oliveira Lima; Romilton Ferreira de Barros Júnior (Revista Brasileira de Saúde e Produção Animal, 2024)
ABSTRACT The aim of this study was to assess the internal quality of free-range eggs available for sale in Alfenas – MG, Brazil, and stored under refrigerated conditions (maximum and minimum temperatures of 9.7 and 6.7 °C, respectively). The experimental design was completely randomized, structured as a 2x5 factorial arrangement involving two types of retail outlets (supermarket (S) and open-air market (OA)) and five storage periods (1, 8, 15, 22, and 29 days), resulting in 10 treatments. Each treatment had six replicates, represented by individual eggs. The following parameters were evaluated: Haugh unit (HU); percentage of egg weight loss (WL%); percentages of albumen, yolk, and shell; yolk index (YI); albumen index (AI); yolk pH; and yolk color. Egg weight loss increased (p<0.05) with the length of the storage period. Eggs acquired from S were deemed to be of inferior quality (HU < 60), in contrast to those obtained from OA (p<0.05). A significant interaction effect was noted for YI (p<0.05), with eggs from S exhibiting higher YI values than those from OA at 15 and 22 days of storage. Additionally, eggs from S had diminished AI values (p<0.05) when compared to those acquired from OA. The yolk color in eggs from S was more intense than that in eggs from OA (p<0.05). A lower yolk percentage was detected in eggs from S relative to those from OA (p<0.05). Therefore, eggs sold in Alfenas – MG, Brazil, from open-air markets possess superior quality compared to those sold in supermarkets.